Colouring the claim: visual code and national allegiance in 120 Battements par minute (Robin Campillo, 2017). - Hartford, Jason (Modern & Contemporary France, 2022)
The visual language of 120 Battements par minute imposes a disciplined approach to colour: specifically, the Tricolore. Blue, white, and red appear in a colour 'chord' that indexes the French flag. This chromatic iconography enables the film to assimilate minoritarian discourses into a French Republican narrative, staking a claim on the French nation on behalf of Act Up-Paris. By placing the national colours strategically within the mise-en-scène, Campillo's film uses the Tricolore to help the audience integrate the characters and plot out of their organizational, medico-sexual, and ethnic specificities and back into the prevailing and exclusionary Republican ideology. Although 120 BPM aligns itself strongly and explicitly with various sexual minority and PWA communities, I argue that its cultural and commercial contexts require it to sidestep possible charges of communautarisme. Faced with the risk of telling the story of an exotic, possibly foreign-inspired movement, the film tells its story through a minoritarian plot and dialogue, while showing it to be patriotically French, through colour. Thus does 120 BPM command authority as a National film, while quietly balancing queer visibility with a claim to integration.